ANALISIS KEBUTUHAN DALAM PROSES PRODUKSI DI PT. CAHAYA GENTALLA MANDIRI DILIHAT DARI ASPEK TENAGA KERJA - Arif, Bery Nur (Jurnal Nosel, 2014)
This research aims at (1) finding the needs process production in PT Cahaya Gentala Mandiri, seen from the input aspect; (2) knowing the needs, seen from the operational processing aspect process production in the PT Cahaya Gentala Abadi and (3) getting the information of the needs from the production aspect point of view in the coolling coil making process in PT Cahaya Gentala Abadi. This research was conducted in PT Cahaya Gental Abadi, Bekasi, West Java. Using evaluative approach, descriptive evaluative research was apllied to conduct the research as the best strategy which most suitable. This research did not use the CIPP models completely but it uses the part of CIPP evaluation model by using IPP evaluation (input, process and product). Using snaw ball sampling, this research applied the technique of data sampling by unlimited or unselected the informan as data resources. There were 38 data sampling which consist of Directors(4), Head of Units (8) and labors (26). Technique of data analisys used in this reasearch wass descriptive analitical techique or non statistic. The result of this research, is: (1) the necessity in this input aspect are: provision of working time that are tailored to the needs and limited by applicable laws, specifically UU no.13 of 2003; policies employee qualifications that are tailored to the needs of the company and to plan training and personal mentoring; Setting standards and workload; Setting standards of tolerance. (2) the necessity in the aspects  of process are: working time which is provided to execute well and discipline, and also supervision of the management company; Managing employees and increase the personal qualifications of the employees by conducting training and personal mentoring; Implementation and workload standards; implementation of standard tolerances established companies to improve labor productivity. (3) the requirement in the aspect of a product is: quality and quantity that should be achieved by optimizing input and process in the company management.